2014
DOI: 10.1007/s10396-014-0585-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumor of gallbladder with liver and retroperitoneal metastases and a good response to the chemotherapeutical treatment

Abstract: Neuroendocrine carcinoma of the gallbladder is an uncommon disease. We present the case of a 45-year-old woman with a mass located in the gallbladder, whose diagnosis was based on contrast-enhanced ultrasound and magnetic resonance imaging. The tumor involved the liver and retroperitoneum, and was histopathologically confirmed by liver biopsy as a neuroendocrine tumor grade 3. The patient received chemotherapy with good response, followed by surgery with cholecystectomy and partial hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A study by the Memorial Sloan Kettering Cancer Center demonstrated that the median survival time of 13 patients with GB-NEC was only slightly shorter compared with that of 435 patients with gallbladder cancer (9.8 months vs. 10.3 months, respectively) (14). Chiorean et al (11) demonstrated that GB-NEC 1-, 2-and 3-year survival rates were lower compared with those of other types of gallbladder cancer (20 vs. 38%; 10 vs. 31%; 0 vs. 30.1%, respectively) during the same period.…”
Section: Prognosismentioning
confidence: 99%
See 3 more Smart Citations
“…A study by the Memorial Sloan Kettering Cancer Center demonstrated that the median survival time of 13 patients with GB-NEC was only slightly shorter compared with that of 435 patients with gallbladder cancer (9.8 months vs. 10.3 months, respectively) (14). Chiorean et al (11) demonstrated that GB-NEC 1-, 2-and 3-year survival rates were lower compared with those of other types of gallbladder cancer (20 vs. 38%; 10 vs. 31%; 0 vs. 30.1%, respectively) during the same period.…”
Section: Prognosismentioning
confidence: 99%
“…To identify the root cause of the GB-NEN, a thorough examination and understanding of the cellular nature of the disease is important. In the process of examination, minimal neuroendocrine cells can be found on the gallbladder mucosa, if any exist in this space (11)(12)(13). Further GB-NEN etiological identifiers may be as follows: i) The undifferentiated gallbladder stem cells separate into neuroendocrine cells.…”
Section: Causesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of liver metastasis is a distinguishing feature of malignant NETs and is an important prognostic factor in patient survival [11]. Surgery has a primary role in the management of neuroendocrine liver metastasis (NELM) and its impact is well appreciated in both curative and palliative settings [12]. The role of chemotherapy and radiotherapy in the management of GB NETs and particularly those developing NELM is equivocal [3]; therefore, surgery remains the best treatment option if complete surgical resection (R0) of NELM can be achieved.…”
Section: Discussionmentioning
confidence: 99%